Responsible Environmental Management: Sustainable Strategy Models for the Future - Lukita, Chandra; Wahyudin Anugrah, Rio; Aulia Anjani, Sheila; Fitriani, Anandha; Mkhize, Thabo (APTISI Transactions on Management (ATM), 2024)
The aim of this study is to explore the relationship between responsible en- vironmental management and business performance, emphasizing sustainable strategy models that enhance both environmental sustainability and profitability in modern organizations. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS, data were collected from 150 medium to large organizations across multiple industries, including manufacturing, retail, and energy sectors, all of which have implemented formal environmental man- agement initiatives. The findings reveal a statistically significant positive impact of responsible environmental management on both environmental sustainability (β = 0.72, p < 0.01) and business performance (β = 0.65, p < 0.01). Addi- tionally, environmental sustainability was found to positively influence business performance (β = 0.54, p < 0.01). These results validate the relevance of models such as the Triple Bottom Line and Circular Economy, providing action- able insights for companies aiming to enhance competitiveness while achieving sustainability goals. This study highlights the practical implications for busi- ness leaders and policymakers, particularly in fostering sustainable practices that align with both regulatory demands and long-term profitability. Future research is recommended to explore the longitudinal impacts of these strategies across different sectors and regulatory environments.